Abnormal directed migration of blood polymorphonuclear leukocytes in rheumatoid arthritis. Potential role in increased susceptibility to bacterial infections - F. Aglas; J. Hermann; G. Egger (Mediators of Inflammation)
Rheumatoid arthritis (RA) patients are at higher risks of bacterial infection than healthy subjects. Polymorphonuclear leukocytes (PMN) are the first line of nonspecific cellular defence against these infections. We tested the hypothesis that abnormal directed migration of PMN may be one reason for the increased infection rate of RA patients. PMN migration was investigated in 68 peripheral blood samples of 15 RA patients compared with 64 samples of healthy controls in a novel whole blood in vitro membrane filter assay. The migration of PMNs from RA patients and controls was stimulated using the bacterial chemoattractant N-formyl-methionyl-leucylphenylalanine (fMLP). Unstimulated PMN migration of RA patients was increased compared with healthy controls as measured by the following parameters: (a) absolute number of migrant PMNs (1954 ± 87 vs. 1238 ± 58 PMN/mm2), (b) percentage of PMNs migrated into the filter (total migration index, TMI) (28.6 ± 0.9 vs. 24.0 ± 0.8 %), (c) the distance half the migrating PMNs had covered (distribution characteristic, DC) (22.6 ± 1.1 vs. 16.1 ± 0.6 mm) and (d) the product of TMI and DC (neutrophil migratory activity, NMA) (669.0 ± 45.0 vs. 389.0 ± 18.9). fMLP stimulated PMNs of RA patients showed defective migration compared to unstimulated samples as shown by (a) a reduced number of migrant PMNs (1799 ± 93 PMN/mm2), (b) lower TMI (26.1 ± 0.9 %), (c) unremarkable altered distribution characteristic (22.9 ± 0.8 mm) and (d) significant reduced migratory activity (600.0 ± 30.0). Our data suggest that the high incidence of infections in RA patients may partly be caused by defective migratory activity of PMNs to bacterial chemoattractants as demonstrated by fMLP.